IN SILICO ANALYSIS ON BINDING ACTION OF TERPENE NATURAL COMPOUNDS FROM APOCYNACEAE FAMILY AGAINST SHV-1 BETA-LACTAMASE FROM Klebsiella pneumoniae - A M Sabbah, Sajida; Indri Astuti, Rika; Budiarti, Sri (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2025)
Antibiotic resistance is a growing threat to public health, particularly with hospital-acquired infections caused by Klebsiella pneumoniae. The limited treatment options for these infections are further complicated by the emergence of antibiotic-resistant strains due to the overuse of antibiotics. This study investigates the potential of Monoterpene Indole Alkaloids (MIAs) derived from six genera within the Apocynaceae family as inhibitors of the beta-lactamase enzyme (bla-SHV-1), which plays a key role in antibiotic resistance in Klebsiella pneumoniae. Using the PyRx program for molecular docking, we assessed the binding affinity and interaction profiles of various MIAs with bla-SHV-1. Our results identified Paucidisine, (-)-19-Oxoisoeburnamine, and Paucidactine A as the most promising candidates, based on their interaction energies and binding modes. Detailed analysis of ligand-protein interactions, including hydrogen bonds and hydrophobic interactions, revealed that these MIAs exhibit higher binding affinity and structural similarity to the native ligand bla-SHV-1. While these findings are promising, it is important to note that they are based on in silico models. Further in vitro and in vivo studies are required to validate the efficacy and safety of these MIAs as potential therapeutic agents. This research marks a significant step towards developing alternative treatment options for antibiotic-resistant Klebsiella infections, potentially improving patient outcomes and addressing the global challenge of antibiotic resistance. In conclusion, our study offers novel insights into the potential use of MIAs as inhibitors of bla-SHV-1, contributing to the ongoing efforts to combat antibiotic resistance. Future research should focus on validating these in silico results through rigorous experimental and clinical studies, considering the ethical implications of introducing new treatments.